Modulatory effects of synbiotic blend on selected human fecal bacteria and TNFα + LPS-induced inflammation in human intestinal epithelial cells - Anita Rawat; Arka Bhattacharya; Rupa Tharu; Ruchika Maurya; Sanjay Kumar Bhadada; Mahendra Bishnoi; Kanthi Kiran Kondepudi (The Microbe)
Leaky gut is characterised by increased gut permeability resulting from dysbiosis which is often associated with various gastrointestinal disorders. Synbiotic formulations (combinations of prebiotics and probiotics) are known to improve microbial balance, promote gut barrier function and to exhibit immunomodulatory properties. In this study, the synbiotic blend (SB) comprising Bifidobacterium longum Bif10, Bifidobacterium breve Bif11, Lacticaseibacillus rhamnosus LAB3, Lactiplantibacillus plantarum LAB39, and isomalto-oligosaccharides (IMOs) was evaluated for its effect on (i) the composition of human fecal microbiota using batch fermentation, specifically focusing on the growth of selected fecal bacterial groups and (ii) its ability to alleviate TNF-α + LPS-induced inflammation in human intestinal epithelial (Caco-2) cells. After 48 h of fecal batch fermentation, SB increased the total viable count of Bifidobacteria (by ∼0.6 log₁₀ CFU/mL) and Lactobacilli (by ∼0.5 log₁₀ CFU/mL), while reducing the counts of E. coli, Klebsiella, and Clostridium by ∼0.4–0.6 log₁₀ CFU/mL, respectively. Short-chain fatty acids (SCFAs), particularly acetate and butyrate, were accumulated after 72 h of fermentation with SB. SB treatment suppressed intracellular ROS production as compared to the TNF-α + LPS-treated Caco-2 cells. SOD, catalase activities and GSH levels were restored (1.5- to 3-fold increases), while levels of IL-1β, TNF-α, IL-6, and IL-8 were reduced by more than 1.5-fold compared to the TNF-α + LPS-treated cells. Furthermore, the expression of tight junction genes (ZO-1, claudin, and occludin) was increased by 1.5- to 2.5-fold, correlating with improved TEER values and reduced FITC-dextran permeability. These findings indicate the potential of this synbiotic blend to enhance selected beneficial gut bacteria and to restore intestinal barrier integrity and function.